PENINGKATAN KETERAMPILAN PROSES SAINS DAN KETERAMPILAN SOSIAL SISWA MELALUI PENERAPAN PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS BERBASIS EKSPERIMEN - Ai Kusnawati; Tjuk Mardianto (CV Putra Publisher, 2022)
Cognitive learning outcomes of students in physics subjects are still low. This indicates that students' science process skills and social skills are low. Therefore, efforts will be made to improve students' science process skills and social skills by applying the experimental-based STAD type cooperative learning model. This research is a classroom action research carried out in three cycles. Observation sheets and worksheets were used to observe science process skills, while the attitude scale questionnaire was used to observe social skills. The increase from one cycle to the next can be determined by using the gain (g) test. The results of classical mastery of science process skills in cycle I was 36.67%, cycle II was 90.00% and cycle III was 96.67%. The results of classical mastery of social skills at the beginning of learning were 50.00% and at the end of learning were 60.00%. The results of the cognitive aspect of cascal completeness in the first cycle were 33.33%, the second cycle was 63.33% and the second cycle was 86.67%. Therefore, it can be concluded that the application of the experimental-based STAD type cooperative learning model can improve science process skills, social skills and student learning outcomes.